Dopamine-mediated photothermal theranostics combined with up-conversion platform under near infrared light. Issue 1 (December 2017) - Lv, Ruichan; Yang, Piaoping; Chen, Guanying; Gai, Shili; Xu, Jiating; Prasad, Paras
Abstract An organic-inorganic hybrid core-shell nanostructure, based on mesoporous silica coated upconversion core-shell nanoparticles (NaGdF4 :Yb, Er@NaGdF4 :Yb@mSiO2 -Dopa abbreviated here as UCNP@mSiO2 -Dopa) that stably incorporates dopamine (Dopa) in the silica layer was introduced as a theranostic nanoplatform for optical imaging guided photothermal therapy (PTT) using NIR excitation. Silica-attaching polyethylenimine make the Dopa transforms into an active form (transferred Dopa) that strongly absorbs light under single 980 nm irradiation. We show that the activated UCNP@mSiO2 -Dopa nanoplatform is able to produce a pronounced photothermal effect, that elevates water temperature from room temperature to 41.8 °C within 2 minutes, while concurrently emitting strong upconverted luminescence (UCL) for visualized guidance under 980 nm laser. In addition, we demonstrate the application of the same UCNP@mSiO2 -Dopa nanoplatform for magnetic resonance imaging (MRI) and x-ray computed tomography (CT) enabled by the gadolinium (Gd) element contained in the UCNP. Importantly, thein vitro andin vivo anti-cancer therapeutic effects have been shown efficacious, implying the use of the described nanoplatform as an effective multi-modal imaging enabled PTT agent. Results from thein vivo biodistribution of UCNPs@mSiO2, cellular live/dead assay, and histologic analysis of main organs of treated mice, reveal that the UCNP@mSiO2 -Dopa agents are bio-compatible with low toxicity.